ANALYSIS AND DEVELOPMENT OF STAFF RETENTION STRATEGIES IN THE CONTEXT OF INCREASING COMPETITION IN THE LABOR MARKET. (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This study focuses on the analysis and development of employee retention strategies in an increasingly competitive labour market. The study also aims to examine the impact of various factors such as corporate culture, professional growth and development opportunities on successful staff retention.